Pengaruh Penambahan Pasir Pada Metode Aerasi Tanah Dalam Stabilisasi Timbal (Pb) - Faiq Pandu Mahajana; Muhammad Abdus Salam Jawwad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Soil contamination by heavy metals, particularly lead (Pb), is a serious environmental issue in Indonesia, as it affects human health, ecosystems, and land productivity. Pb can accumulate in plants and enter the food chain, increasing public health risks. Therefore, an effective, low-cost, and field-applicable remediation method is required. One potential approach is aeration, which involves oxygen addition to improve soil porosity and enhance heavy metal stabilization. However, the effectiveness of aeration is strongly influenced by soil physical properties; hence, this study focuses on the effect of soil–sand composition on Pb stabilization in Inceptisol soil. The research was conducted using a laboratory-scale batch reactor with Inceptisol soil contaminated by Pb(NO₃)₂ (300 mg/kg). Treatments included three soil–sand ratios (100:0, 70:30, and 60:40) and three aeration durations (non-aerated, 12 hours, and 24 hours). Parameters analyzed were residual Pb²⁺ concentration and soil physical characteristics, with data processed using two-way ANOVA. Results showed that sand addition improved aeration effectiveness, achieving the highest Pb removal (94,6%; final Pb 17,1 mg/kg) at 60:40 composition with 24-hour aeration. In contrast, pure soil without aeration showed the lowest effectiveness (76,1%). Statistical tests confirmed that media composition, aeration duration, and their interaction significantly affected Pb stabilization (p < 0,05). This study demonstrates that combining aeration with sand addition offers a simple and practical method for remediating Pb-contaminated Inceptisol soil.